Nursing of a patient with essential hypertension and severe anxiety treated with Traditional Chinese Medicine meridian-collateral measuring system combined with auricular acupoint pressing therapy (经络仪联合耳穴压丸治疗1例原发性高血压合并重度焦虑患者的护理体会) - ZHAO Jiaying (赵佳莹); ZHANG Shuqi (张树琦); YU Juan (于娟); HAO Yangyang (郝杨杨); ZHANG Xueyuan (张学媛); GUO Yanbing (郭雁冰); SONG Xueping (宋雪苹) (中西医结合护理)
This paper summarizes the nursing experience of a patient with essential hypertension and severe anxiety. By testing the twelve meridians of the patients through the Meridian-Collateral measuring instrument, the auricular acupoint pressing therapy by syndrome differentiation, in combination with daily life guidance, emotional care, psychological counseling and health education, were carried out to reduce blood pressure, relieve anxiety, and improve the quality of life of the patient. (本文总结经络仪检测联合耳穴压丸治疗1例原发性高血压合并重度焦虑患者的护理体会。患者入院后完善护理评估, 基于经络仪检测数据, 辨证取穴进行耳穴疗法, 同时加强生活起居护理, 指导患者饮食和运动, 并配合中医情志护理, 进而稳定控制患者的血压, 缓解其焦虑、眩晕症状。)